BAHAN BAKAR NABATI SEBAGAI SALAH SATU ALTERNATIF UNTUK MENDUKUNG PENGGUNAAN BAHAN BAKAR â€RAMAH LINGKUNGANâ€ - Nanny Kusminingrum (Jurnal Jalan-Jembatan, 2008)
Activities using motor vehicle by society is increasing. This phenomena can cause air pollution from the vehicleâ€™s engine. This waste from motor-vehicle is known as one of the main elements that form pollutant. Alternative energy supply and usage program is a temporary solution, aimed not only to find a more environment-friendly fuel, but also to reduce subsidy for fossil-fuel (oil), and to find a cheaper but more efficient and renewable sources of energy. One potensial energy source to be developed in in Indonesia is biofuel. Biofuel that can be used to substitute gasoline comes from plants that are already well-known by Indonesian people Therefore, development and usage-implementation of renewable and environment-friendly fuel needs proper attention. Coordination between the Government, private sector, and farmer is needed, with each parties functionally support each other in the processes from the resource supply, production activity, and market distribution. Key words : Air Pollution, Motor vechicle , Biofuel, fossil fuel, environment friendly